APLIKASI VALUE ENGINEERING PADA RUMAH TINGGAL TIPE 90/180, 135/180, DAN 223/253 DI PERUMAHAN BLIMBING PERMAI KOTA MALANG - Haris Asta Pradana, Sumardi, Udi Subagyo (Prokons: Jurnal Teknik Sipil, 2015)
The application of value engineering to Blimbing Permai Residence (BPR) aimed to sistematically organize and apply a technique that identifies the product to meet the required function at the lowest price. It was applied to houses of 90/180, 135/180, and 223/253 at BPR without lowering the price. Pareto and function analysis method were employed to analize some phases of work plan to result in some more objective alternatives based on several variables. Both methodes result in breakdown cost in a chronological order of the highest itemized work cost to the lowest one. The analyses result in some work items possibly to replace, they are of wall, roof, truss, and concrete slab works of 90/180 type; masonry, truss, and roff tiling of 135/180 type; concrete, wall and roofing of 225/253 type. The Value Engineering result in hebel bricks to replace conventional ones; ceramic concrete slab to replace conventional concrete one ; light galvanic to replace wooden truss ; granite tile to replace marble ones. Its a result type 90/180 is more economical at IDR.250,292,433.03 or 10.5 % of the existing IDR.276,591,438.78. The type 135/180 is more economical at IDR.346,840,945.04 or 11.07 % of the existing IDR.385,047,844.51. At last of type 223/253 is more economical at IDR.595,156,885.77 or 17.08 % of the existing IDR.667,232,563.47.Keywords: breakdown cost, function analysis, Pareto Analysis, value engineering